Lease Contract as a Means of Financing Investment in Algerian Legislation: a Theoretical & Practical Study from a Legal & Economic Perspective - نابتي , عبد الحق يوسف (Milev Journal of Research and Studies, 2019)
The difficulties of financing economic projects through bank borrowing are the most important factors that led to the emergence of leasing as a financing method, which varies after it appears in response to the diversification of the financial needs of the economic institution. Leasing has seen considerable prosperity because of its importance in overcoming the most important difficulties of bank financing; which is mainly the problem of slow procedures for obtaining the loan, and guarantees for this, and partial funding. This technique was adopted as a means of financing investment in Algeria in 1996 under Ordinance No. 96-90 on rental dependence. Its rules allowed competitive advantages in comparison to other financing means of tenants, lessors and suppliers, and their impact on the Sustainable development of the national economy as a whole. In this study, we tried to study the effectiveness and efficiency of Algerian legislation for the performance of the leasing system in its effective and efficient role.